Service quality: Implications for management practice in higher education institution (off-site campus: students) - Hamedon, Siti Rohimi; Saad, Nurulwahida; Nik Idris, Nik Ruzni (s.n, 2012)
The notion of the incompatibility of service quality and higher education is changing fast in Malaysia. Stakeholders are becoming more discriminating in selecting institution of higher learning. A group of stakeholder are student, as customers from off-site campus. This study is to explore and examine the perception of IIUM service users particularly the off campus students at Nilai, Petaling Jaya and Kuantan campus with regards to the services they received from three dimensions. The aim is to address the areas needing improvement and provide recommendations on what needs doing